2017
DOI: 10.5424/sjar/2017153-9899
|View full text |Cite
|
Sign up to set email alerts
|

What role will climate change play in EU agricultural markets? An integrated assessment taking into account carbon fertilization effects

Abstract: Recent studies point to climate change being one of the long-term drivers of agricultural market uncertainty. To advance in the understanding of the influence of climate change on future agricultural market developments, we compared a baseline scenario for the year 2030 with alternative simulation scenarios that differ regarding: (1) emission scenarios; (2) climate projections; and (3) the consideration of carbon fertilization effects on crop growth. For each simulation scenario, the CAPRI model provides globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Based on our analysis, derived from a series of global gridded biophysical and climate model ensembles coupled with a global agricultural market model, it can be concluded that market adjustments are important when analysing climate change impacts in the agricultural sector. Our results are in line with the findings of Nelson et al (2014), Baldos and Hertel (2015), Blanco et al (2017) and Martinez et al (2017), who emphasize the importance of considering agricultural market interactions when analysing the overall impacts of climate change on the agricultural sector. As we consider a larger scenario ensemble and consistently different combinations of climate and biophysical models within a global context, our analysis can be considered more robust than previous ones.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Based on our analysis, derived from a series of global gridded biophysical and climate model ensembles coupled with a global agricultural market model, it can be concluded that market adjustments are important when analysing climate change impacts in the agricultural sector. Our results are in line with the findings of Nelson et al (2014), Baldos and Hertel (2015), Blanco et al (2017) and Martinez et al (2017), who emphasize the importance of considering agricultural market interactions when analysing the overall impacts of climate change on the agricultural sector. As we consider a larger scenario ensemble and consistently different combinations of climate and biophysical models within a global context, our analysis can be considered more robust than previous ones.…”
Section: Discussionsupporting
confidence: 93%
“…adjust the production depending on the price elasticities estimated by Jansson and Heckelei (2011). Accordingly, CAPRI is suitable for a comprehensive analysis of climate change effects considering market adjustments and was used in several multimodel assessments at global level (Hasegawa et al 2018, Van Meijl et al 2018, and has also been used before to assess the impacts of climate change on EU agriculture (Shrestha et al 2013, Delincé et al 2015, Martinez et al 2017. However, in the previous studies focusing on the EU, projections for non-EU regions were mainly based only on a single crop growth model and the analysis was primarily done at EU aggregated level and not considering regional aspects (for instance, differentiating between Northern and Southern European impacts).…”
Section: Methodsmentioning
confidence: 99%
“…Whilst, as described above, the index does not extensively integrate metrics related to agriculture or the food system, results show many EU countries are more exposed to climate-related risks than the global average. Martinez et al (2017) use agro-economic and climate models to explore near-future impacts of global crop yield and price changes on the EU. Despite large regional variations, overall average global production for staple crops increases due to CO 2 fertilisation effects.…”
Section: Assessments Of the Eu As A Regional Blocmentioning
confidence: 99%
“…Benzie et al (2019) provide examples of some existing mechanisms for integrating concerns about TCRs such as the EU Civil Protection Mechanism, EU Adaptation Strategy, Water Framework Directive, EU Cohesion Fund and Structural Funds. Some authors suggest that harmonised trade policy and trade adjustments through market mechanisms will be adequate to mitigate against agricultural yield and price changes (Martinez et al, 2017;Hertel and Baldos, 2016;Elbehri et al, 2015). However, uncertainty exists overall in the role of trade, and thus trade policy, in mitigating food price volatility (Ferguson and Gars, 2020).…”
Section: Opportunities For Future Researchmentioning
confidence: 99%